Phosphate mediated regulation of carbohydrate metabolism in Neurospora crassa - M. Sonavaria; P. Padgaonkar; B. G. Nair; H. S. Chhatpar (Fungal Genetics Reports, 1985)
Phosphate mediated regulation of carbohydrate metabolism in Neurospora crassa